2019
DOI: 10.1093/ibd/izy384
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab in Combination With Corticosteroids for Induction Therapy in Crohn’s Disease: A Post Hoc Analysis of GEMINI 2 and 3

Abstract: Background Combined therapy with vedolizumab and corticosteroids may improve clinical response or remission in Crohn’s disease. The aim of this study is to assess efficacy and safety/tolerability of vedolizumab plus stable doses of corticosteroids at baseline during induction therapy in moderately to severely active Crohn’s disease. Methods A post hoc exploratory analysis was performed on data from GEMINI 2 (NCT00783692) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…Six studies (reported in 13 articles) were included in the qualitative synthesis and in the quantitative synthesis, as follows: Infliximab (four studies): NCT00094458 (SONIC) [ 23 26 ], NCT02096861 (PLANET CD) [ 6 , 27 ], NCT02148640 (NOR-SWITCH) [ 28 , 29 ], NCT02883452 (CT-P13 SC trial) [ 19 ]. Vedolizumab (two studies): NCT00783692 (GEMINI 2) [ 30 33 ], NCT01224171 (GEMINI 3) [ 31 , 32 , 34 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies (reported in 13 articles) were included in the qualitative synthesis and in the quantitative synthesis, as follows: Infliximab (four studies): NCT00094458 (SONIC) [ 23 26 ], NCT02096861 (PLANET CD) [ 6 , 27 ], NCT02148640 (NOR-SWITCH) [ 28 , 29 ], NCT02883452 (CT-P13 SC trial) [ 19 ]. Vedolizumab (two studies): NCT00783692 (GEMINI 2) [ 30 33 ], NCT01224171 (GEMINI 3) [ 31 , 32 , 34 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Vedolizumab (two studies): NCT00783692 (GEMINI 2) [ 30 33 ], NCT01224171 (GEMINI 3) [ 31 , 32 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…At weeks 6 and 10, patients who were randomized to receive vedolizumab had 15.2% (week 6) and 26.6% (week 10) clinical remission, while patients who received placebo had 12.1% (week 6) and 12.1% (week 10) clinical remission (p = 0.433, p = 0.001, respectively). 27 …”
Section: Biologics In Crohn’s Diseasementioning
confidence: 99%
“…Pivotal studies in UC (GEMINI-1) and CD (GEMINI 2) found 1/895 (0.11%) death due to acute coronary syndrome and 1/1115 (0.09%) death due to myocarditis in a male patient with a history of DVT [ 34 , 35 ]. Neither the post hoc analysis of GEMINI 2 and GEMINI 3 trials, nor long-term trials of GEMINI LTS, found cases of CVEs or VTE even when VDZ was associated with CSs [ 36 , 37 , 38 ]. A recent VARSITY trial, which compared VDZ with adalimumab, recorded only one case out of 383 (0.26%) patients treated with VDZ with superficial thrombophlebitis [ 39 ].…”
Section: Pharmacological Therapiesmentioning
confidence: 99%